Orthoboard: An orthopaedic app for medical education - Goh, Kian Liang; Noor Rahin, Mohd Shahidan; Abdul Razak, Ardilla Hanim; Awang, Mohd Shukrimi; Abdul Rahman, Ahmad Zulhairi (2018)
This is a hybrid mobile app developed by our team based on the undergraduate Orthopaedic curriculum to deliver clinical knowledge and skills. The app consisted of core and practical orthopaedic information with step-by-step visual-guided slides to perform orthopaedic procedures in the clinical settings. A social messaging platform is integrated in the app to encourage discussion and interactive learning. The highlight of the app is the integration of Islamic input in medical practice which is the ﬁrst for medical apps.